Foreign aid and development in South Korea and Africa : a comparative analysis of economic growth - Kalu, Kelechi Amihe; Kim, Jiyoung (Professor of political science) (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book compares the rapid development of South Korea over the past seventy years with selected countries in sub-Saharan Africa to assess what factors contributed to the country's success story, and why it is that countries which were comparable in the past continue to experience challenges in achieving and sustaining economic growth. In the 1950s, South Korea's GDP per capita was $876, roughly comparable with that of Cote d'Ivoire and somewhat below Ghana's. The country's subsequent transformation from a war-ravaged, international aid-dependent economy to the 13th largest economy in the world has been the focus of considerable international admiration and attention. But how was it that South Korea succeeded in multiplying its GDP per capita by a factor of 23, whilst other Less Developed Countries continue to experience challenges? This book compares South Korea's politics of development and foreign assistance with that of Ghana, Nigeria, and Zambia, which were also major recipients of U.S. aid, to investigate the specific contexts that made it possible for South Korea to achieve success. Overall, the book argues that effective state capacity in South Korea's domestic and international politics provided an anchor for diplomatic engagement with donors and guided domestic political actors in the effective use of aid for economic development. This book will be of interest to researchers and students working on development, comparative political economy, and foreign aid, and to policy makers and practitioners looking for a greater understanding of comparative development trajectories"--
Introduction: Politics, Institutions, Donor and Recipient Relationships -- South Korea: A Case of Effective Aid -- Ghana: A Case of Aid Success? -- The Politics of U.S. Aid to Nigeria -- Zambia: Aid Dependency and Dependent Development -- Myanmar: A Sub-Saharan African Case in Southeast Asia -- A Comparative Analysis of Foreign Aid and Development in South Korea and African Countries -- Conclusion: Toward Sustainable Donors and Recipients Partnership.
Keywords: Economic assistance -- Korea (South) -- History; Economic assistance -- Africa -- History; Economic development -- Korea (South) -- History; Economic development -- Africa -- History; SOCIAL SCIENCE / Third World Development